NoFumo+: Mobile Health App to Quit Smoking Using Cognitive-Behavioral Therapy - Patricia García-Pazo; Joana Fornés-Vives; Albert Sesé Abad (Nursing Research and Practice)
This paper describes the development and test of a smartphone application to quit smoking using cognitive behavioral therapy (CBT). The tool includes recommendations from US Clinical Practice Guidelines (USCPG), drawing on the potential of smartphones and complying with the health App (mHealth) assessment standards. The mHealth created, called NoFumo+, is structured by 4 weeks treatment, implements the USCPG 5A recommendations (ask, advise, assess, assist, and arrange) and incorporates a CBT. It also includes complementary information, monitoring of the smoking behavior, social support for users, proposals for alternative activities to smoking, and innovative gamification to encourage and reward adherence. To technical development, a multidisciplinary team was formed (healthcare, research, and software engineers) that made theoretical decisions on both technical issues and the incorporation of therapeutic techniques. The validation was carried out in two phases; the first in the laboratory by a group of experts in information and communication technologies and CBTs (n = 15) and the second, a field study with smokers (n = 10). The standards for the development of mHealth recommended by the Andalusian Healthcare Quality Agency and the App quality evaluation guidelines of the Catalonian ICT Foundation for Social Health were used as assessment protocols by the experts’ panel and the smokers’ group, respectively. Experts’ assessment results were satisfactory and some improving changes were suggested, such as to add more gamification elements. The group of smokers rated the mHealth as 100% easy to use and effective for quit smoking and understandable by the 83.3%. They also found No Fumo + quite useful to have the information available at all times. The obtained evidence after a complete two-phased validation study, with experts and potential users, shows a mHealth with high quality and easy to use. Finally, investigation project registered in ClinicalTrials.gov with reference to this trial is registered with NCT045402004.